Age alone is not a contraindication to kidney donation: Outcomes of donor nephrectomy in the elderly. Issue 8 (20th June 2018) - Serrano, Oscar K.; Yadav, Kunal; Bangdiwala, Ananta; Vock, David M.; Dunn, Ty B.; Finger, Erik B.; Pruett, Timothy L.; Matas, Arthur J.; Kandaswamy, Raja
Abstract: With increasing organ demand, living kidney donation from older donors (>60‐years‐old) has become more common. Between 1975 and 2014, 3752 donor nephrectomies (DN) were performed at University of Minnesota; 167 (4.5%) were >60‐years‐old Short‐ and long‐term outcomes were compared between contemporaneous >60‐years‐old and <60‐years‐old donors. On univariate analysis, >60‐years‐old were more likely to have had prior abdominal surgery and hypertension; and less likely to smoke. Baseline estimated glomerular filtration rate (eGFR) was lower in >60‐years‐old (80 ± 16 vs 101 ± 26 mL/min/1.73 m 2 ; P < .001). Intraoperative and postoperative complications were similar, except a higher prevalence of <30 day ileus (3% vs 7%; P = .021) and longer postoperative length of stay (LOS) (4.2 vs 4.6 days; P = .005). On multivariate analysis, <30 day ileus and LOS continued to be significantly greater for >60‐years‐old After >20 years post‐DN, systolic blood pressure was significantly higher among >60‐years‐old (142 vs 125 mm Hg; P < .001) and HTN was diagnosed earlier (9 vs 14 years). After donation, eGFR was significantly lower for >60‐years‐old but slope of eGFR and rates of end‐stage renal disease (ESRD) were not significantly different >20 years post‐DN. Thus, kidney donation among carefully selected >60‐years‐old poses minimal perioperative risks and no added risk of long‐term ESRD.